Riverbend Gap [large type] - Hunter, Denise, 1968- (Hunter, Denise, 1968- Riverbend romance, 2021)
"When Katie Loveland's car veered off a winding Appalachian Mountain road, she thought she was done for. That is until Cooper Robinson, local sheriff's deputy, came to her rescue. And though Katie narrowly escaped her brush with death, she still fell. Hard. She wasn't the only one. But soon Cooper learns that the woman he's more attracted to than any he's ever met is his brother's new girlfriend -- and therefore unquestionably off limits. Yet, despite his best efforts, Cooper and Katie can't seem to avoid running into each other. Or ignore the undeniable chemistry between them. As they grow closer, Katie shares the secrets of her past and the real reason she moved to their small North Carolina town. She also wins over Cooper's welcoming and bighearted family. But they don't know that her feelings for Cooper keep growing -- all while she's dating his brother. Soon the stakes of their emotional connection become higher than either of them could have imagined. Katie stands to lose the first family she's ever had, and a scandal could doom Cooper's campaign for sheriff's office. Suddenly they find themselves on the edge of another precipice -- and they're forced to make a decision that could change their lives forever"-- Provided by publisher.